Frequency of Factor Associated with Persistent Pulmonary Hypertension in Newborn Attending Bachakhan Medical Complex/ Gajju Khan Medical College Swabi - Shah Jehan; Kaleem Ullah; Muhammad Musa; Asaad Ullah; Sijad ur Rehman; Khan, Muhammad Hanif (Indus Journal of Bioscience Research, 2025)
Background and Objective: Persistent pulmonary hypertension of the newborn (PPHN) is a life-threatening condition characterized by failure of normal circulatory transition after birth, leading to elevated pulmonary vascular resistance and hypoxemia. This study aimed to determine the frequency of maternal, intrapartum, and neonatal factors associated with PPHN in neonates presenting to Bachakhan Medical Complex/ Gajju Khan Medical College Swabi. Methods: A hospital-based descriptive cross-sectional study was conducted from 25 February 2025 to 25 May 2025. Seventy-eight neonates with echocardiographically confirmed PPHN were enrolled using consecutive non-probability sampling. Data on maternal, intrapartum, and neonatal variables were collected using a structured proforma and analyzed using descriptive statistics. Results: The majority of neonates were term (78.2%) and male (57.7%). Maternal factors included preeclampsia (30.8%), gestational diabetes mellitus (23.1%), and oligohydramnios (19.2%). Intrapartum factors included meconium-stained amniotic fluid (33.3%), emergency cesarean section (37.2%), and prolonged labor (26.9%). Neonatal factors included low Apgar score (44.9%), birth asphyxia (41.0%), and need for resuscitation (38.5%). Echocardiography showed elevated pulmonary artery pressure in all cases, with right-to-left shunting via ductus arteriosus (59.0%) and foramen ovale (50.0%). Conclusion: There is a strong association between perinatal hypoxic stress and development of PPHN. Early recognition of high-risk pregnancies and prompt neonatal resuscitation are essential to improve outcomes, particularly in resource-limited settings.